Necessity and feasibility of developing diagnosis and treatment guidelines for cirrhotic ascites and hepatorenal syndrome with Chinese intellectual property rights - LIU Jianjun; ZHENG Wenkai; GAO Tingting; WANG Jianghong; REN Yanjun; LIU Jianguo; LIU Changlin (Zhongguo linchuang yanjiu, 2023)
At pressent, there are many controversies in China about the recommendations in Diagnosis, Evaluation, and Management of Ascites, Spontaneous Bacterial Peritonitis and Hepatorenal Syndrome (hereinafter referred to as the “Guidelines”) revised in 2021, and it's believed that some clauses lack theoretical support. Some researches in China have showed that sodium restriction and negative sodium balance are the only reason for hyponatremia. Sodium retention is the stress protective reaction mechanism for hyponatremia, not the basis for sodium restriction treatment. This article dialectically evaluates the relationship between peripheral circulation dysfunction, hepatorenal syndrome pathogenesis and diagnosis and treatment, and believes that the AASLD Guidelines have weakened the clinical guiding significance, and looks forward to the development of ascites and hepatorenal syndrome diagnosis and treatment guidelines with Chinese intellectual property rights and in line with Chinese clinical practice.